STRATEGIC COMPETENCY AFFECTING BUSINESS SUCCESS OF YOUNG AGROPRENEURS - Maheran Katan; Nur Melissa Binti Mohammad Faisal Wee; Nur Fatihah Binti Malik (International Journal of Accounting, Finance and Business, 2021)
This is a conceptual paper to study the effect of strategic competency on businesssuccess of agropreneurs SMEs in Malaysia. Agriculture is one of the most essential industrythat plays a role primarily as the food provider and helps generate income for the country.Malaysia is still being anchored as a net importer of agricultural products. The increase infood import is due to the lack of intensive efforts in improving food production particularly indeveloping successful agropreneurs. It is imperative to study the competency needed forsuccessful agropreneurs. The objective of this paper is to examine the influence of strategiccompetency on agropreneurial business success. This study developed a conceptual modelwithin the context of Resources Based View Theory (RBV) which claims that entrepreneur’scompetencies are key resources of the firms that are valuable and competent entrepreneurs maylead to business success. This study provides vital information to agropreneurs, policy makers,and contributes significantly to the existing body of knowledge in the scope of strategiccompetency on the business success of Malaysian SMEs in the agricultural sectors.